Sistem Informasi Pengaduan Sosial Pada Dinas Sosial Kota Malang - Nolawangi, Baiq Farida; Sakaria, Setiabudi; Aditya, Addin (J-INTECH (Journal of Information and Technology), 2020)
Website is one of the supporting tools as a medium of information and promotion on the internet. With a website, everyone from all over Indonesia and the world can easily get information about the company or agency. Social service agency has a special task to carry out some of the government's general tasks and development in the field of Social Welfare. From social problems that occur, it is difficult for the community to convey problems that occur around the community environment. The many social problems that occur in the community are known from public complaints which are usually done via telephone or DM Instagram. The impact of social problems include juvenile delinquency, poverty, unemployment, missing people, homeless people, and people with mental disorders. The purpose of this study was to build a Social Handling Information System in Malang City Social Service. To create a website / information system, you can use CodeIgniter (CI), CodeIgniter is an application development framework (Application Development Framework) using PHP, is a framework for working or making programs using PHP that is more systematic. Malang City Social Service has many tasks, one of which is handling several complaints from the people of Malang City. The author proposes to raise a theme "Information Systems for Social Assistance for Web-Based Communities to Facilitate the Receipt of Social Service Reports in Malang". In this information system there are 3 main menus, namely: complaints, survey reports, and data results. In the complaints menu the user can input the complaint data which will later be processed by the social service staff themselves. On the survey report page the staff section can check the data and make changes to the system status. On the data results page the staff can make changes to the data. Before making a complaint to the system, the community must first register by entering the NIK. Complaints submitted by the public will automatically be entered into the system. With this information system, it is hoped that it can help the performance of the Malang city social services and also help report complaints from the people of Malang.